'The importance of planning for the future': Burden and unmet needs of caregivers' in advanced heart failure: A mixed methods study. (April 2018) - McIlfatrick, Sonja; Doherty, Leanne C; Murphy, Mary; Dixon, Lana; Donnelly, Patrick; McDonald, Kenneth; Fitzsimons, Donna
Background: While studies have evaluated caregiver outcomes in heart failure, the burden and support needs when caring for someone with advanced heart failure at the end of life have yet to be outlined. Aim: To identify psychosocial factors associated with caregiver burden and evaluate the support needs of caregivers in advanced heart failure. Design: A sequential mixed methods study comprising two phases: (1) postal survey with advanced heart failure patients and their caregivers and (2) interviews with current and bereaved caregivers. Correlation, chi-square, t test, regression and thematic analysis were undertaken on the data. Participants: Advanced heart failure patients ( n = 112) and their caregivers ( n = 84) were recruited from secondary care settings across the United Kingdom and Ireland. For phase 2 interviews, current caregivers ( n = 20) were purposively recruited from phase 1, and bereaved caregivers ( n = 10) were purposively recruited via voluntary organisation, social media and email. Results: More than half the caregivers (53%) had levels of distress associated with depression (Zarit Burden score >24). Caregiver depression score, preparedness for caregiving and patients' depression score predicted caregiver burden. Qualitative analysis identified an overarching theme of lack of future care planning and four subthemes: (1) seeking emotional support from someone who understands, (2) want information on prognostication, (3) lack of knowledge on how to and where to get support and (4) require knowledge on what to expect at the end of life. Conclusion: Caregivers have unmet needs and feel unprepared for the future. Implementation of future care planning by clinical teams should address patient and caregiver support needs and in turn alleviate caregiver burden.